EFEKTIVITAS KEBIJAKAN PENGENDALIAN ALIH FUNGSI LAHAN PERTANIAN MENJADI NON PERTANIAN DALAM MENJAGA KETAHANAN PANGAN DAERAH DI KABUPATEN SRAGEN - Ageng Arroum Aminuddin; Satria Aji Imawan (Journal of Management and Public Policy, 2026)
The conversion of agricultural land into non-agricultural uses has become a strategic issue that continues to increase along with regional development and economic demands, including in Sragen Regency, which is recognized as one of the main foodproducing areas in Central Java. Sragen Regency was selected as the research location due to the high pressure from residential, industrial, and infrastructure development that potentially reduces the extent of productive agricultural land. This study aims to analyze the effectiveness of policies controlling the conversion of agricultural land as well as the factors contributing to land-use change in Sragen Regency. This study employs a qualitative approach with a descriptive method, using in-depth interviews, observation, and documentation involving the National Land Agency, the Department of Agriculture, the Department of Housing and Spatial Planning (Disperkimtaru), the Department of Industry, Agricultural Extension Officers, and the Farmers and Fishermen Association. The analysis of policy effectiveness is based on Riant Nugroho’s policy implementation accuracy framework, which includes policy accuracy, implementer accuracy, target accuracy, environmental accuracy, and process accuracy, supported by a theoretical framework to map the factors driving agricultural land conversion. The findings indicate that policies controlling the conversion of agricultural land in Sragen Regency are supported by a relatively strong regulatory framework and demonstrate alignment between central and local government policies. However, their implementation has not yet been fully effective. This is reflected in the continued occurrence of land conversion in certain areas due to economic pressures, population growth, and regional development orientation. This study recommends strengthening cross-sectoral supervision, ensuring consistency in policy implementation, and enhancing the protection of productive agricultural land to support regional and national food security.